The science of animal growth and meat technology - Lonergan, Steven Michael; Topel, David G.; Marple, Dennis Neil, 1945- (Academic Press, an imprint of Elsevier, 2019)
This book combines fundamental science-based and practical concepts relating to the prenatal and postnatal growth of cattle, sheep, and pigs. It provides the necessary components to understand the production and growth of livestock for safe and quality meat products and presents an understanding of the principles of meat science and technology. Information on the slaughter process of animals, muscle structure and meat tenderness, meat quality, meat safety, and microbiology are included in this reference text.--adapted from publisher's description.